2022
DOI: 10.1212/wnl.0000000000200271
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Type I Interferon Signaling in Muscle Stem Cell Proliferation During Dermatomyositis

Abstract: Background and objective:The idiopathic inflammatory myopathy Dermatomyositis (DM) is an acquired disease that combines muscle, lung and skin impairments. DM patients show a wide range of severity of proximal skeletal muscle weakness, associated with inflammatory infiltrates, vasculitis, and capillary dropout, perifascicular myofiber atrophy. Moreover, DM muscles show signs of muscle regeneration. Since muscle stem cells (MuSCs) are responsible for myofiber repair, we asked wether the proliferative properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Analysis of muscle biopsies from dermatomyositis patients showed that in the advanced stage of perifascicular atrophy there is a perturbation of MRFs expression, characterized by an increase in Pax7 and Myogenin, but not MyoD [ 128 ]. Recently, a study showed that MuSCs isolated from muscle biopsies of patients with dermatomyositis have reduced proliferation and differentiation compared with healthy controls [ 129 ]. These cells exhibit higher levels of senescence markers that could partly explain their proliferative defects ( Figure 2 ).…”
Section: Inflammatory and Infectious Myopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of muscle biopsies from dermatomyositis patients showed that in the advanced stage of perifascicular atrophy there is a perturbation of MRFs expression, characterized by an increase in Pax7 and Myogenin, but not MyoD [ 128 ]. Recently, a study showed that MuSCs isolated from muscle biopsies of patients with dermatomyositis have reduced proliferation and differentiation compared with healthy controls [ 129 ]. These cells exhibit higher levels of senescence markers that could partly explain their proliferative defects ( Figure 2 ).…”
Section: Inflammatory and Infectious Myopathiesmentioning
confidence: 99%
“…These cells exhibit higher levels of senescence markers that could partly explain their proliferative defects ( Figure 2 ). Considering that dermatomyositis is associated with sustained inflammation characterized by high levels of IFN-I [ 126 ], the authors performed loss- and gain-of-function experiments to demonstrate that high levels of IFN-I decrease the proliferation of MuSCs, while pharmacological inhibition of IFN signaling rescued the proliferation of MuSCs from dermatomyositis patients [ 129 ]. These findings suggest that the detrimental effect of dermatomyositis in MuSC function is mediated, at least in part, by paracrine factors.…”
Section: Inflammatory and Infectious Myopathiesmentioning
confidence: 99%
“…Immunohistochemical co-expression of MxA with vascular endothelial growth factor (VEGF) and MxA staining on tubuloreticular inclusions (TRIs) supported IFN1 pathway activation as an underlying mechanism for dermatomyositis vasculopathy and TRI formation [3,60–62]. IFN1 exposure decreased muscle stem cells’ (MuSC) proliferation; impaired myoblasts differentiation and fusion; induced myotubes atrophy and IFN-α production; and impaired endothelial cells angiogenesis [60,63,64 ▪▪ ]. Blocking IFN1-signaling cascade via Janus kinase signal transducer and activator of transcription (JAK-STAT) pathway activation by antiinterferon alpha-beta receptor, anti-IFN-α, anti-IFN-β, and ruxolitinib (preferentially JAK1 and JAK2 inhibitors), prevented and reversed these effects in muscle and endothelial cells [64 ▪▪ ,65 ▪ ,66,67].…”
Section: Dermatomyositis-specific Antibody and Interesting Updatesmentioning
confidence: 99%
“…IFN1 exposure decreased muscle stem cells’ (MuSC) proliferation; impaired myoblasts differentiation and fusion; induced myotubes atrophy and IFN-α production; and impaired endothelial cells angiogenesis [60,63,64 ▪▪ ]. Blocking IFN1-signaling cascade via Janus kinase signal transducer and activator of transcription (JAK-STAT) pathway activation by antiinterferon alpha-beta receptor, anti-IFN-α, anti-IFN-β, and ruxolitinib (preferentially JAK1 and JAK2 inhibitors), prevented and reversed these effects in muscle and endothelial cells [64 ▪▪ ,65 ▪ ,66,67]. Interestingly, normal MuSC showed proliferation defect after exposure to dermatomyositis MuSC culture medium supernatant; adding ruxolitinib into the medium prevented the proliferation defect [64 ▪▪ ].…”
Section: Dermatomyositis-specific Antibody and Interesting Updatesmentioning
confidence: 99%
“…In a study in the current issue of Neurology® , Gallay et al 8 provide further evidence of the importance of the IFN-I pathway in the pathogenesis of dermatomyositis by (1) delineating toxic effects of IFN-β on dermatomyositis-derived human skeletal muscle myoblasts and (2) reverting pathogenic effects of IFN-β with nonspecific (JAK/STAT inhibitors) and specific (blockade of the IFN-I receptor) IFN-I–pathway inhibitors.…”
mentioning
confidence: 99%